Commentary: Narrative Conceptualizations of Student Engagement (LEARNing Landscapes, 2007)
This commentary explores what it might mean to conceptualize student engagement narratively, that is, by conceptualizing it in terms of the curricula that children and teachers are living out in classrooms. It draws on recent school-based narrative inquiries and earlier theoretical work on curriculum making as negotiating a curriculum of lives. Thinking narratively about student engagement puts lives at the centre of curriculum making and calls forward questions about educators’ purposes and intentions in schools.
Keywords: curriculum of lives; educator purporse; curriculum making; student engagement; narrative